Composition and structure dependence of specific heat of disordered iron-palladium alloys. (October 2017) - Xiao, Fei; Fukuda, Takashi; Yamaguchi, Takashi; Sato, Kazunori; Kakeshita, Tomoyuki
Abstract: Depending on Pd content, disordered Fe-Pd alloys take various crystal structures: body-centered cubic (BCC), body-centered tetragonal (BCT), face-centered tetragonal (FCT) and face-centered cubic (FCC) structures. We have measured specific heat of Fe-Pd alloys to understand the lattice stability and electronic state of the alloys. At the phase boundary between FCT and FCC phases, electronic specific heat coefficient shows a local maximum and the Debye temperature shows a local minimum. A local maximum of electronic specific heat coefficient also appears in the BCC region with Pd content of near 10 at.%. Graphical abstract: Electronic specific heat coefficient and Debye temperature of Fe-Pd alloys depend significantly on crystal structure.